Acute Hemiballismus as the Presenting Feature of Parietal Lobe Infarction - Patel, Avani R (Cureus, 2019)
It is widely believed that hemiballismus and chorea are suggestive of a basal ganglia subthalamic nucleus lesion; however, this not a rule. We report the case of a 63-year-old male with complaints of slurred speech, increased movement of the left half of his body, and headache. He had diabetes, hypertension, and a past medical history of stroke with residual weakness over the right side of his body. The patient developed the sudden onset of irregular, large amplitude, increased involuntary movements of his left upper and lower limbs with a flinging pattern. His blood sugar and serum osmolality were normal. His magnetic resonance imaging (MRI) showed an acute right parietal lobe infarction. Patients can experience hemiballismus with lesions other than the subthalamic nucleus in the basal ganglia. This is contrary to the classic belief that hemiballismus is associated with, and only with, lesions in the subthalamic nucleus. This manuscript describes a case of hemiballismus occurring in a patient secondary to a parietal lobe infarction.